2008
DOI: 10.1091/mbc.e07-06-0604
|View full text |Cite
|
Sign up to set email alerts
|

Isc1p Plays a Key Role in Hydrogen Peroxide Resistance and Chronological Lifespan through Modulation of Iron Levels and Apoptosis

Abstract: The inositolphosphosphingolipid phospholipase C (Isc1p) of Saccharomyces cerevisiae belongs to the family of neutral sphingomyelinases that generates the bioactive sphingolipid ceramide. In this work the role of Isc1p in oxidative stress resistance and chronological lifespan was investigated. Loss of Isc1p resulted in a higher sensitivity to hydrogen peroxide that was associated with an increase in oxidative stress markers, namely intracellular oxidation, protein carbonylation, and lipid peroxidation. Microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 66 publications
5
109
0
Order By: Relevance
“…2 Interestingly, ironinduced yeast death might involve Isc1p, a neutral sphingomyelinase that can be activated by cardiolipin and is involved in the biosynthesis of ceramide. 31 In fact, In addition, death of old cells within the colony center feeds the young cells at the colony margin (colony differentiation). The death of chronologically old cells preserves resources, releases nutrients, and allows adaptive regrowth (chronological aging), whereas replicatively old cells die for the good of young cells, which inherit the undamaged cellular material upon cellular division (replicative aging).…”
Section: Triggering Yeast Apoptosismentioning
confidence: 99%
“…2 Interestingly, ironinduced yeast death might involve Isc1p, a neutral sphingomyelinase that can be activated by cardiolipin and is involved in the biosynthesis of ceramide. 31 In fact, In addition, death of old cells within the colony center feeds the young cells at the colony margin (colony differentiation). The death of chronologically old cells preserves resources, releases nutrients, and allows adaptive regrowth (chronological aging), whereas replicatively old cells die for the good of young cells, which inherit the undamaged cellular material upon cellular division (replicative aging).…”
Section: Triggering Yeast Apoptosismentioning
confidence: 99%
“…Ceramide is a known bioactive lipid and has been shown to play an important role in cell processes such as growth, death, senescence, and response to stress (2,3). ISC1-deficient budding yeast exhibits a slower growth rate than wild type (WT) 2 strains (4) and higher sensitivity to high salt (NaCl) and hydrogen peroxide (5,6). A genome-wide screen revealed that ISC1 deletion (isc1⌬) mutants were sensitive to the DNA alkylating agent methyl methanesulfonate (MMS) and to the DNA replication blocking drug hydroxyurea (HU) (7).…”
mentioning
confidence: 99%
“…A very recent work found that Isc1p played a key role in oxidative stress resistance and chronological lifespan (23). The study showed that Isc1p regulated cellular redox homeostasis through modulation of iron levels.…”
Section: The Yeast Nsmase: Isc1mentioning
confidence: 95%